MiR-4500 is epigenetically downregulated in colorectal cancer and functions as a novel tumor suppressor by regulating HMGA2. Issue 11 (1st November 2016) - Yu, Feng Yan; Tu, Yun; Deng, Ying; Guo, Cancan; Ning, Jue; Zhu, Yuzhen; Lv, Xiaohua; Ye, Hua
ABSTRACT: This study aimed to understand the exact function and potential mechanism of miR-4500 in colorectal cancer (CRC). In this study, the expression of miR-4500 was decreased in both CRC cells and tissues, and downregulated miR-4500 indicated advanced tumor stage and poor survival. By bisulfite sequencing analysis, we found that the CpG island in the promoter region of miR-4500 was hypermethylated in CRC cells and tissues compared with normal control cells and non-tumor tissues, respectively. Functionally, gain- and loss-of-function analyses indicated the tumor suppressor role of miR-4500: it suppressed cell proliferation, cell cycle progression, migration, and invasion. Predictive algorithms and experimental analyses identified HMGA2 as a direct target of miR-4500. Reintroducing HMGA2 impaired the inhibitory effects of miR-4500 on cell growth and motility. Clinically, higher HMGA2 protein expression in CRC tissues was associated with advanced tumor stage and poor survival. An inverse correlation was found between miR-4500 levels and HMGA2 protein expression. Taken together, this study provides the first evidence that miR-4500 functions as a novel tumor suppressor in the miR-4500/HMGA2 axis in colorectal carcinogenesis, and restoring miR-4500 expression might represent a promising therapeutic strategy for CRC.